Qualitative analysis of controlled release ciprofloxacin/carbopol 934 mucoadhesive suspension - Subhashree Sahoo; Chandra Kanti Chakraborti; Subash Chandra Mishra (Wolters Kluwer Medknow Publications, 2011)
Mucoadhesive polymeric (carbopol 934) suspension of ciprofloxacin was prepared by ultrasonication and optimized with the aim of developing an oral controlled release gastro-retentive dosage form. The qualitative analysis of the formulation was performed by fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray powder diffraction (XRD), and scanning electron microscopy (SEM) analyses. FTIR (400 cm-1 to 4000 cm-1 region) and Raman (140 to 2400 cm-1 region) Spectroscopic studies were carried out and the spectra were used for interpretation. XRD data of pure drug, polymer and the formulation were obtained using a powder diffractometer scanned from a Bragg's angle (2q) of 10° to 70°. The dispersion of the particle was observed using SEM techniques. The particle size distribution and aspect ratio of particles in the polymeric suspension were obtained from SEM image analysis. The results from FTIR and Raman spectroscopic analyses suggested that, in formulation, the carboxylic groups of ciprofloxacin and hydroxyl groups of C934 undergo a chemical interaction leading to esterification and hydrogen bonding. The XRD data suggested that the retention of crystalline nature of ciprofloxacin in the formulation would lead to increase in stability and drug loading; decrease in solubility; and delay in release of the drug from polymeric suspension with better bioavailability and penetration capacity. The SEM image analysis indicated that, in the formulation maximum particles were having aspect ratio from 2 to 4 and standard deviation was very less which provided supporting evidences for homogeneous, uniformly dispersed, stable controlled release ciprofloxacin suspension which would be pharmaceutically acceptable.